PENGARUH BERPIKIR POSITIF TERHADAP KECEMASAN MAHASISWA DALAM MENGERJAKAN SKRIPSI - Syifa Salsabila; Dinda Permatasari Harahap; Meutia Nauly; Fillia Dina Anggraeni (LPPM Universitas Cipta Mandiri, 2026)
Final-year students often experience anxiety that affects their performance, especially during th processof writing their theses. This study aimed to examine the effect of positive thinkig on anxiety amongstudents at University of Pembangunan Panca Budi Medan. The research method used wasquantitative. The population in this study consisted of 120 students writing theses in the managementprogram at University of Pembangunan Pancabudi Medan, and a sample of 48 students was selectedusing purposive sampling. Data were collected using a positive thinking scale and an anxiety scale. Theresults of the study indicated a negative effect of positive thinking on anxiety, with a simple linearregression value (rxy) of -0.574 and p = 0.000 < 0.05, thus acceptiong the hypothesis. Data analysisshowed that anxiety levels were high (Hypothetical Mean 70 < Empirical Mean 85.75), with thedifference exceeding one standard deviation (9.836). conversly, positive thinking levels were low(Hypothetical Mean 60 > Empirical Mean 45.19), with the difference exceeding one standard deviation(6.903). The result of the study suggested that positive thinking can be an effective strategy to overcomethe anxiety experienced by studente while working on their theses. These findings provide importantcontributions to the field of psychology, particularly in efforts to improve students’ mental well-being.